Diseño de una máquina lanzadora de balones de voleibol para entrenamiento en prácticas deportivas en la Fundación Universidad de América (2020)
The main objective of the project was to design a volleyball ball throwing machine for training in sports practices at the University of America Foundation. For this, an analysis was made of the world of volleyball, such as history, regulations, types of throws and the physics involved in these releases, in addition to mentioning worldwide selections that have implemented this type of machines in their training and also mention the types of machines that are currently on the market, with this the technical specifications and prices of each of these are detailed. From this, the functional mode of these teams is taken as a reference to set the design parameters according to the requirements and needs of the volleyball team of the Fundación Universidad de América.